Organizational Change Communication, Workplace Bullying and Job Insecurity: The Moderating Role of Trust in Management - Pika Handayani; Reni Rosari; Miftachul Mujib (Universitas Negeri Malang, 2023)
This study aims to examine the relationship between organizational change communication and workplace bullying on job insecurity, as well as investigate the moderating role of trust in management. The objects of this research were employees who work in companies affected by Covid-19 in Indonesia, particularly in the tourism, banking, education, and entertainment sectors. The data were obtained through a survey by distributing questionnaires using a purposive sampling technique to 174 respondents, and it was analyzed using the partial least square structural equation modeling (PLS-SEM). The results of the study showed that organizational change communication has a negative effect on job insecurity, workplace bullying has a negative effect on job insecurity, and trust in management moderates the positive effect of workplace bullying on job insecurity. However, there is no moderating effect of trust in management on organizational change communication and job insecurity. There are some limitations and suggestions discussed in this paper. Keywords: Organizational change communication, workplace bullying, trust in management, job insecurity